Assessment of the severity of periodontal disease in upper premolars compared to the lower premolar teeth in canine patients - Larraín N., Yanira (2017)
The aim of the present study was to assess the severity of periodontal disease in upper premolars compared to the lower premolars in canine patients older than one year old at the Small Animal Clinic of the Faculty of Veterinary Medicine of the Universidad Nacional Mayor de San Marcos, during the period October 2012 to March 2013. All teeth of 54 dogs were evaluated using the Veterinary Periodontal Index to stablish the presence and severity of periodontal disease. The results showed that 81.5% of dogs had some degree of periodontal disease and 40% of teeth were affected with some degree of periodontal disease. Moreover, there was an association between the presence of periodontal disease in tooth premolars and the maxillary or mandibular region, where periodontal disease was more frequent in the upper premolars.